2018
DOI: 10.3892/mmr.2018.9104
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by Bigelovii A through inhibition of NF‑κB activity

Abstract: Bigelovii A is a 30-nortriterpenoid glycoside, isolated from Salicornia bigelovii Torr. Until now, the effect of Bigelovii A on breast cancer treatment was unknown. The present research indicated that Bigelovii A significantly inhibited the proliferation of human breast cancer cells (MCF-7, MDA-MB-231 and MDA-MB-468) in a concentration-dependent manner. It was particularly effective in MCF7 cells, with an IC50 value of 4.10±1.19 µM. The anti-proliferative effect of Bigelovii A was ascribed to the induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Other researchers found that inhibiting the activation of NF-κB restrained the increased permeability of epithelial cells induced by TNF-α. 18 In this study, activated NF-κB did not upregulate the permeability of monolayers but inhibited NF-κB downregulated the permeability, suggesting that the activity of the NF-κB signaling pathway is closely related to the permeability of pancreatic duct epithelial cells and the epithelial barrier.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Other researchers found that inhibiting the activation of NF-κB restrained the increased permeability of epithelial cells induced by TNF-α. 18 In this study, activated NF-κB did not upregulate the permeability of monolayers but inhibited NF-κB downregulated the permeability, suggesting that the activity of the NF-κB signaling pathway is closely related to the permeability of pancreatic duct epithelial cells and the epithelial barrier.…”
Section: Discussionmentioning
confidence: 51%
“…Since phosphorylation is necessary for the transcriptional activity of p65, p-p65 is more important to indicate the activation of NF-κB. 18 The results above indicated that TNF-α activated the expression and phosphorylation of p65. On the other hand, in the cells treated with PDTC for 1.5 hours, p65 mRNA expression detected by qPCR was downregulated compared with the TNF-α group (Fig.…”
Section: Tnf-α Activated the Nf-κb Signaling Pathway And Pdtc Inhibimentioning
confidence: 89%
“…Bigelovii A inhibited the growth of HL-60, MCF-7, and HepG2 cell lines, with IC 50 values of 6.18, 78.08, and 13.64 μM, respectively. Bigelovii A also exhibited strong cytotoxic effects against several breast cancer cell lines (MCF-7, MDA-MB-231, and MDA-MB-468), and induced apoptosis by downregulating the NF-kB signaling genes Cyclin D1 and COX-2 [ 203 ]. Known compounds of 30-nortriterpenoid and oleanane-type triterpenoid glycosides were also isolated from Salicornia bigelovii , but only the 3- O -β- D -glucuropyranosyl-30-norolean-12,20-(29)-dien-28-oic-acid-28- O -β-d-glucopyranoside was cytotoxic-active against HL-60 cell lines, with an IC 50 value of 31.87 μM [ 202 ].…”
Section: New Anticancer Agents From Halophytesmentioning
confidence: 99%
“…Zhang et al demonstrated that Rb1 has a protective effect on DCM by inhibiting caspase family proteins and NF⁃κB pathway ( Zhang et al, 2021 ), which is similar to the protective effect of Rb1 on MI/R ( Figure 3C ; Fan et al, 2020 ; Yan et al, 2014 ). NF⁃κB is a key factor in triggering inflammatory response and regulating apoptotic response, and its phosphorylation and acetylation are indicative of mitochondria-dependent apoptotic signals ( Guan et al, 2018 ). The expression level of silent information regulator 1 (Sirt1) increased significantly after Rb1 stimulation, suggesting that it can activate Sirt1 ( Zhang et al, 2021 ).…”
Section: Protective Effect Of Panax Ginseng On Dia...mentioning
confidence: 99%